Fenomena Ekonomi Indonesia Dimasa Pemilihan Umum Calon Presiden Tahun 2024 - Deanita Sari; Laila Surayya (Al-Buhuts, 2024)
The execution of the General Election for Presidential Candidates was expected to have a substantial impact on the country's economy, aiming to increase Indonesia's Gross Domestic Product. The election's effect extends beyond technical matters to fundamental aspects. The 2024 General Election process will be a crucial moment that will influence the state of the Indonesian economy. The research method used is qualitative research on phenomena. This research will focus on analyzing the economic implications of the election, using secondary data obtained from statistical sources available on the web (www.bps.go.id). The study will specifically look into the areas of economic equilibrium, labor costs, mining, manufacturing and construction, tourism, banking, insurance, and finance.  The initial findings indicate that these sectors experienced economic growth during the 2024 General Election for Presidential Candidates. However, prices, particularly the producer price index, witnessed a decrease. There was also an increase in the National Trade Price Index and Inflation, leading to economic weakness, especially in the areas of Transportation, International Trade, and the Balance of Payments. The research aims to provide insights into the economic phenomena associated with the election and its potential effects on Indonesia's Gross Domestic Product.